A new method for the theoretical analysis of electroforced sedimentation using Terzaghi-Voigt combined model - Jami, Mohammed Saedi; Iwata, Masashi (Taylor & Francis Group, LLC, 2008)
In this article a new method for the theoretical analysis of electroforced sedimentation (EFS) by use of the Terzaghi-Voigt combined model is presented. Zinc oxide and a mixture of zinc oxide and KC-flock are used as experimental materials. Both the electro-osmotic pressure gradient Epg and the modified consolidation coefficient Ce of the materials are assumed to be constant. The analytical solution can explain the solid compressive pressure distribution with time and position. The progress of electroforced sedeimentation can be represented by an average consolidation ratio Uc as in mechanical expression. Variations of the effectiveness of EFS with the percentage of KC-flock in the mixture, electric current density, and total solid volume per unit cross-sectional area are investigated. EFS is best applied for materials with permanent charge.